Active labor market policies and crime - Torben Tranaes (IZA World of Labor, 2015)
Active labor market programs continue to receive high priority in wealthy countries despite the fact that the benefits appear small relative to the costs. This apparent discrepancy suggests that the programs may have a broader purpose than simply increasing employment—for instance, preventing anti-social behavior such as crime. Indeed, recent evidence shows that participation in active labor market programs reduces crime among unemployed young men. The existence of such effects could explain why it is the income-redistributing countries with greater income equality that spend the most on active labor market programs.
Keywords: I38; K42; 330; the economics of crime; activation; workfare; marginalized youth